Learning a trade a craftsman's notebooks, 1955 - 1997 - Price, Reynolds 1933-2011 (Duke Univ. Press, 1998)
Whether Price is reflecting on the rhythm of his day-to-day writing process or ruminating about the central character in what would become, for instance, Kate Vaiden - should she be a woman; what would be her name; why would the story be told in the first person? - he envelops the reader in the task at hand, in the trade being practiced. Instead of personal memoir or a collection of literary fragments, Learning a Trade presents what Price has called the "ongoing minutes" of his effort to learn his craft
Keywords: Price, Reynolds <1933-> -- Notebooks, sketchbooks, etc; Price, Reynolds -- 1933-2011; Authorship -- Problems, exercises, etc; Tagebuch -- 1955-1997